2014
DOI: 10.3354/meps10918
|View full text |Cite
|
Sign up to set email alerts
|

Predator chemical cues increase growth and alter development in nauplii of a marine copepod

Abstract: Copepods are a fundamental trophic link in the marine food web. While much attention has been devoted to the role of temperature and food for copepod development and growth, little is known about how marine copepods adjust their life history according to the prevailing predation risk. This is striking, considering the potential advantage of risk-sensitive life history, and the many reports of freshwater zooplankton showing strong effects of risk cues on growth and development. Here, we measured growth and deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 64 publications
1
31
0
Order By: Relevance
“…The lack of response to cues in our experiments is, however, consistent with the almost entirely lack of reports on behavioral effects of kairomones in marine zooplankton and copepods. Thus, Buskey et al (2012) in a review failed to find evidence of predator-induced responses for marine zooplankton, and only three studies were identified in the review by Heuschele and Selander (2014) in addition to Bjaerke et al (2014), of which only two report effects on feeding-related behavioral changes (reduced swimming speed or reduced gut fullness with predator cues (van Duren and Videler 1996;Cieri and Stearns 1999). There is also one report that diurnal vertical behavior can be induced by the presence of fish, but the cue that elicited the response was not identified, except that it was not of chemical nature (Bollens and Frost 1989).…”
Section: Induced Responses and Phenotypic Plasticitymentioning
confidence: 99%
“…The lack of response to cues in our experiments is, however, consistent with the almost entirely lack of reports on behavioral effects of kairomones in marine zooplankton and copepods. Thus, Buskey et al (2012) in a review failed to find evidence of predator-induced responses for marine zooplankton, and only three studies were identified in the review by Heuschele and Selander (2014) in addition to Bjaerke et al (2014), of which only two report effects on feeding-related behavioral changes (reduced swimming speed or reduced gut fullness with predator cues (van Duren and Videler 1996;Cieri and Stearns 1999). There is also one report that diurnal vertical behavior can be induced by the presence of fish, but the cue that elicited the response was not identified, except that it was not of chemical nature (Bollens and Frost 1989).…”
Section: Induced Responses and Phenotypic Plasticitymentioning
confidence: 99%
“…The role of chemical cues as a reliable source of information is often doubted in marine environments with strong advection. But marine copepods have predator induced responses, such as reduced feeding activity (Cieri and Stearns 1999) or altered development and growth (Bjaerke et al 2014) in response to predator-derived chemicals, or increased diel vertical migration (Bollens and Frost 1989) and even reversed diel vertical migration (Ohman et al 1983). Mechanical and visual stimuli, as for instance predator encounter, may also induce risk-sensitive behavioral reactions (Bollens et al 1994).…”
Section: Drivers Of Diapause and Migration Timing: The Copepod Casementioning
confidence: 99%
“…Similarly, reduced growth rate prolongs reaching sexual maturity and increases the risk of habitat desiccation. While some animals can decrease their encounter rate with a predator through slowing down their growth (Bjærke, Andersen, & Titelman, ), the gape limitation of tilapiines instead represents an achievable size refuge for killifish, facilitating acceleration in the growth rate. However, the unpredictable environmental conditions also strongly support tendency toward a fast growth (Blažek et al., ) and therefore act in concert with the pressure from the predator.…”
Section: Introductionmentioning
confidence: 99%
“…While some animals can decrease their encounter rate with a predator through slowing down their growth (Bjaerke, Andersen, & Titelman, 2014), the gape limitation of tilapiines instead represents an achievable size refuge for killifish, facilitating acceleration in the growth rate.…”
mentioning
confidence: 99%